Principal Academic Supervision Management in Improving the Pedagogic Competence of Vocational School Teachers - Ahmad Rival Anshori; Wiwik Dyah Andayani (Journal of Science and Education (JSE), 2025)
This study investigates the management of academic supervision by principals at SMKN 1 and SMKN 2 Leles, Cianjur Regency, in improving teachers’ pedagogic competence. Using a qualitative case study design, the research involved principals, vice principals, and vocational subject teachers as key informants. Data were collected through participatory observation, in-depth interviews, and document analysis, and were analyzed using Miles, Huberman, and Saldaña’s interactive model. The findings indicate that supervision planning at both schools is supported by structured annual programs, standardized observation instruments based on pedagogic competence indicators, and participatory decision-making involving senior teachers and management teams. Implementation integrates clinical supervision techniques and reflective feedback to enhance lesson planning, classroom management, and assessment practices. Evaluation and follow-up mechanisms demonstrate progress toward evidence-based decision-making; however, the absence of standardized impact assessment tools limits the measurement of supervision outcomes on student learning. Supporting factors include leadership commitment, teacher motivation, and adequate facilities, while inhibiting factors involve limited training, inconsistent follow-up, and weak integration of supervision results into broader school development plans. The study concludes that effective academic supervision management in vocational schools should combine strategic planning, consistent implementation, data-driven evaluation, and sustainable follow-up, tailored to the unique characteristics of the vocational education context.